“Rather a manager and networker than a researcher”: converging technologies in the clinic. - Vadrot, Alice B.M. (Innovation: The European Journal of Social Sciences, 2013)
Technological developments brought about new approaches to and new insight into the functioning of the brain and neurological disorders. More specifically, advancement in the areas of neuroimaging, genomic technologies and molecular biology is conceived as a pathway to more differentiated diagnosis and appropriate treatment. In this regard, the convergence of technologies in the area of health care and medical research has significantly increased during the past two decades. The aim of this article is to better understand how the convergence of technologies in the field of neuroscience takes place at the micro-level of knowledge production, namely the clinic. It is based on the results of an ethnographic study conducted at an Epilepsy Monitoring Unit in Vienna. I start from the assumption that the convergence of technologies in the diagnosis and treatment of epilepsy anticipates a specific means of knowledge production that impacts on the understanding and definition of neurological conditions and the identity of patients and medical doctors simultaneously. One important result concerns the scientization of the way that people with epilepsy perceive, explain and understand epilepsy and the brain. On the one hand respective narratives seem to support the scientific definition of epilepsy; on the other, the failure of seizure control tends to induce a specific understanding of the brain as having unpredictable and uncontrollable mastery over body, memory and soul.